Зигзаги демократизации политического режима в Украине - Куценко, О. (Социология: теория, методы, маркетинг, 2005)
The article is dedicated to discussion of the main features of political regime trans formation in postSoviet Ukraine. In definition of political regime the author follows the actorcentered neoinstitutional approach that allows to focus on individual and collective social practices determined by actor’s interests, situation, and strategy of action as well as limited by actor’s habitues, social skills, resources, and rules. The author argues an illiberal democratic character of formal political regime, which was embodied in the middle of 1990s in Ukraine, and discusses the zigzags of its future development. The question about social and political factors of the “Orange Revolution” explosion is also examined.